Studi Pengaruh Penggunaan Gadget terhadap Tumbuh Kembang Anak pada Pasien Klinik Tumbuh Kembang - Olivia Dwimaswasti; Rony Agusta Pudjianto; Betty Windasari; Apriani Tiaraningtias; Hilda Amalia; Moh Heri Kurniawan (Faletehan Health Journal, 2026)
Children aged five and under are often overexposed to gadgets, despite the fact that early childhood is a critical period for cognitive, language, motor, and socio-emotional development. Uncontrolled gadget exposure is feared to negatively impact children's growth and development. The purpose of this study was to determine the relationship between gadget use and child development. This study used an observational analytical design with a cross-sectional approach. The sampling technique used was total sampling with a sample size of 30 children patient aged 3-5 years. The study was conducted from January 2-15, 2024 in a growth and development clinic. Data were analyzed using the Spearman statistical test. The results of this study showed that the majority of children used gadgets daily (76.7%) with a frequency of use three times per day (33.3%). Developmental measurements showed that the majority of children were in the developmental deviation category (83.3%). The results of the statistical test showed a significant relationship between gadget use and developmental disorders (p-value 0.007). The more frequently a child uses gadgets, the greater the likelihood of experiencing developmental disorders (r = 0.480). Limiting and monitoring gadget use is necessary to prevent disruption to a child's development. Parents, healthcare professionals, and the government need to work together to create an environment that supports optimal child growth and development.